23‐1: Distinguished Student Paper: Flexoelectric Effect on Image Flickering of Fringe Field Switching LCDs. Issue 1 (May 2016) - Chen, Haiwei; Peng, Fenglin; Hu, Minggang; Wu, Shin‐Tson
Abstract : We investigated the flexoelectric effect of a fringe field switching liquid crystal (LC) cell and characterized the resultant image flicker with different LC mixtures and frame rates. Incorporating with human eye perception of 10 observers, we found that LC mixtures with a dielectric anisotropy smaller than ∼7 lead to unnoticeable image flicker at 60 frames per second. The obtained flicker sensitivity line serves as important guidelines for optimizing LC materials and display devices.